Incumbent and entrant response to regulated competition: Signaling with accounting costs and market prices (2001)
Relative prices charged by incumbents have become a strategic issue as competition is introduced into regulated markets which were previously served by a monopoly supplier. We report on the behavior of the incumbent and entrants in the residential UK gas market, where the regulator has made several investigations into whether the incumbent's relative prices constitute undue discrimination. We identify the regulator's policy, the strategic use of cost allocation by both the regulator and the incumbent, and the costs implied by entrants' prices. We deduce that the entrants' behavior provides support for the incumbent's cost allocation arguments rather than those of the regulator. © 2001 Elsevier Science Inc. All rights reserved.